Method for producing ion-exchange glass, mixture for ion exchange, and device for producing ion-exchange glass

By using alkali metal silicate and molten salt for ion exchange during the manufacturing process of ion exchange glass, the problems of productivity reduction and equipment corrosion caused by the increase in dissolution ion concentration are solved, and high-quality and efficient ion exchange glass manufacturing is achieved.

CN113716880BActive Publication Date: 2025-02-11NIPPON ELECTRIC GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110567167.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-04
Filing Date
2021-05-24
Publication Date
2025-02-11
Estimated Expiration
2041-05-24

AI Technical Summary

Technical Problem

In the mass production process of ion exchange glass, when multiple batches of glass are repeatedly ion exchanged by the same molten salt, the concentration of dissolved ions gradually increases, resulting in difficult ion exchange processing, reduced productivity, and metal equipment is prone to corrosion. Impact product quality.

Method used

The ion exchange mixture containing alkali metal silicate is used for ion exchange. The alkali metal silicate and the dissolution ions in the molten salt are ion exchanged to inhibit the increase in the concentration of dissolution ions, and determine whether to add alkali by measuring the stress characteristics of the glass. Metal silicates to prevent metal corrosion.

Benefits of technology

It effectively suppresses the deterioration of production equipment and the decline in product quality, improves productivity, and ensures the stability of the stress characteristics of ion exchange glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113716880B_ABST
    Figure CN113716880B_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing ion-exchange glass, which can achieve both high productivity and prevention of deterioration of production equipment. The method for producing ion-exchange glass comprises a step of immersing a part or all of an ion-exchange glass containing an alkali metal component in an ion-exchange mixture to perform an ion-exchange treatment, and the method comprises a step of adding an alkali metal silicate as an additive to a molten salt to obtain the ion-exchange mixture, wherein the alkali metal silicate contains an alkali metal component that can perform ion exchange with the alkali metal component dissolved from the ion-exchange glass into the molten salt during the ion-exchange treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing ion-exchange glass, an apparatus for producing ion-exchange glass and a mixture for ion exchange. Background Art

[0002] In recent years, chemically strengthened glass that has been subjected to ion exchange treatment has been used in the protective glass of display devices. Such ion exchange treatment is usually performed by immersing the glass in a molten salt and exchanging ions in the glass with ions in the molten salt having different ion radii. For example, the ion exchange treatment is performed by dissolving Li ions in the glass into the molten salt and introducing Na ions or K ions in the molten salt into the glass, or by dissolving Na ions in the glass into the molten salt and introducing K ions in the molten salt into the glass.

[0003] In the mass production process of ion exchange glass, the same molten salt is used to repeatedly perform such ion exchange treatment on multiple batches of glass. As a result, the ions dissolved from the glass (hereinafter referred to as dissolved ions) gradually accumulate in the molten salt, and the concentration of dissolved ions in the molten salt gradually increases. When the concentration of dissolved ions is too high, the above-mentioned ion exchange treatment becomes difficult to perform, resulting in a problem of reduced productivity.

[0004] In order to solve such a problem, a technology has been developed to adjust the concentration of dissolved ions by adding phosphates to molten salts (for example, Patent Document 1). In the technology disclosed in Patent Document 1, alkali metal phosphates such as Na3PO4 and K3PO4 are added to molten salts, and the phosphates absorb the dissolved ions in the molten salts, thereby suppressing the increase in the concentration of dissolved ions in the molten salts.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: U.S. Patent Application Publication No. 2018 / 0362399 Summary of the invention

[0008] Technical problem that the invention aims to solve

[0009] However, when phosphate is added as in Patent Document 1, the metal constituting the device such as the fixture for holding the molten salt tank or the glass is corroded by the phosphate, resulting in the problem that the production equipment is easily deteriorated. In addition, the metal corrosion products will adhere to the glass, which may cause the produced ion exchange glass products to be defective.

[0010] An object of the present invention is to provide a method for producing ion-exchange glass, an ion-exchange mixture, and an ion-exchange glass producing apparatus that can maintain product quality, that is, have high productivity, and prevent deterioration of production equipment.

[0011] Technical solutions to the problem

[0012] <1> The method for producing ion-exchange glass according to the present invention is characterized in that the method comprises a step of immersing a part or all of an ion-exchange glass containing an alkali metal component in an ion-exchange mixture to perform an ion-exchange treatment, wherein the ion-exchange mixture contains a molten salt and an alkali metal silicate as an additive, the alkali metal silicate containing an alkali metal component that can perform ion exchange with the alkali metal component dissolved from the ion-exchange glass into the molten salt during the ion-exchange treatment.

[0013] <2> exist <1> In the method for manufacturing ion-exchange glass, the alkali metal component dissolved from the ion-exchange glass into the molten salt during the ion exchange treatment is preferably Li ion, and the alkali metal silicate includes at least one selected from Na2SiO3, Na4SiO4, Na2Si2O5 and Na2Si4O9.

[0014] <3> exist <2> In the method for producing ion-exchange glass, it is preferred that the glass for ion exchange is alkali aluminosilicate glass and contains 1.0 mol % or more of Li2O as a composition, and the molten salt contains one or more selected from NaNO3 and KNO3.

[0015] <4> exist <1> In the method for manufacturing ion-exchange glass, the alkali metal component dissolved from the ion-exchange glass into the molten salt during the ion exchange treatment is preferably Na ion, and the alkali metal silicate includes at least one selected from K2SiO3, K4SiO4, K2Si2O5 and K2Si4O9.

[0016] <5> exist <1> In the method for manufacturing ion-exchange glass, the alkali metal component dissolved from the ion-exchange glass into the molten salt during the ion exchange treatment is preferably Na ion, and the alkali metal silicate includes at least one selected from Li2SiO3, Li4SiO4, Li2Si2O5 and Li2Si4O9.

[0017] <6> exist <4> or <5> In the method for producing ion-exchange glass, it is preferred that the glass for ion exchange is alkali aluminosilicate glass and contains 1.0 mol % or more of Na2O as a composition, and the molten salt contains KNO3.

[0018] <7> exist <1> ~ <6> In any one of the methods for producing ion-exchanged glass, the alkali metal silicate is preferably a powdery alkali metal silicate crystal.

[0019] <8> exist <7> In the method for producing ion-exchanged glass, it is preferred that the average particle size D50 of the powdered alkali metal silicate is 10 to 1000 μm.

[0020] <9> exist <7> or <8> The method for producing ion-exchanged glass preferably further comprises a step of stirring the molten salt after adding the alkali metal silicate to the molten salt.

[0021] <10> exist <1> ~ <9> In the method for producing an ion-exchanged glass described above, it is preferred that the amount of the alkali metal silicate added is 0.1 to 30 parts by mass based on 100 parts by mass of the molten salt.

[0022] <11> exist <1> ~ <10> In the method for manufacturing ion-exchange glass described in any one of the items, it is preferred that multiple batches of ion-exchange glass are sequentially immersed in the ion-exchange mixture to perform multiple ion-exchange treatments, and the method for manufacturing ion-exchange glass also includes: a step of measuring the stress characteristics of the ion-exchange glass obtained in the last ion-exchange treatment after ion-exchange treatment of a predetermined number of batches of ion-exchange glass; and a step of determining whether to add alkali metal silicate to the molten salt based on the measurement results of the stress characteristics.

[0023] <12> exist <11> In the method for manufacturing ion-exchange glass, it is preferred to measure the surface compressive stress of the glass as a stress characteristic. When the surface compressive stress is less than a predetermined threshold value, ion exchange of the next batch of ion-exchange glass is carried out after adding alkali metal silicate to the molten salt. When the surface compressive stress is greater than the predetermined threshold value, ion exchange of the next batch of ion-exchange glass is carried out without adding alkali metal silicate to the molten salt.

[0024] <13> The ion exchange mixture according to the present invention preferably contains a molten salt and an additive, wherein the molten salt contains at least one selected from NaNO 3 and KNO 3 , and the additive contains an alkali metal silicate.

[0025] <14> exist <13> The ion exchange mixture preferably contains 0.1 to 30 parts by mass of an alkali metal silicate as an additive, based on 100 parts by mass of the molten salt.

[0026] <15> exist <13> or <14> In the ion exchange mixture, the alkali metal silicate is preferably a powdery alkali metal silicate crystal, and the alkali metal silicate contains at least one selected from Na2SiO3, Na4SiO4, Na2Si2O5 and Na2Si4O9.

[0027] <16> exist <13> or <14> In the described mixture for ion exchange, the alkali metal silicate is preferably a powdery alkali metal silicate crystal, and the alkali metal silicate contains at least one selected from Li2SiO3, Li4SiO4, Li2Si2O5 and Li2Si4O9.

[0028] <17> The ion exchange glass manufacturing device according to the present invention is characterized in that it comprises: <13> ~ <16> The mixture for ion exchange according to any one of the above; and a storage tank for storing the mixture for ion exchange, wherein at least a part of a contact surface of the storage tank with the mixture for ion exchange is made of metal.

[0029] <18> <17> The ion-exchange glass manufacturing apparatus described above preferably further comprises a jig that holds the ion-exchange glass and is immersed in the ion-exchange mixture, wherein a surface of the jig that contacts the ion-exchange mixture is made of metal.

[0030] <19> exist <17> or <18> In the ion exchange glass manufacturing device, the metal is preferably stainless steel.

[0031] Effects of the Invention

[0032] According to the inventions according to <1> to <19>, it is possible to suppress deterioration of production equipment and reduction in product quality compared to the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the ion-exchange glass manufacturing apparatus according to the first embodiment of the present invention.

[0034] Figure 2 This is a flowchart showing an outline of the method for producing ion-exchanged glass according to the first embodiment of the present invention. DETAILED DESCRIPTION

[0035] (First Embodiment)

[0036] Hereinafter, a method for producing ion-exchanged glass, an apparatus for producing ion-exchanged glass, and a mixture for ion exchange according to a first embodiment of the present invention will be described.

[0037] Figure 1This is a schematic diagram of an ion exchange glass manufacturing apparatus according to a first embodiment of the present invention. The ion exchange glass manufacturing apparatus 1 is a processing apparatus for performing ion exchange processing on ion exchange glass G1 to obtain ion exchange glass GX. The ion exchange glass manufacturing apparatus 1 includes an ion exchange mixture 10 , a storage tank 11 , and a jig 12 .

[0038] The ion-exchange mixture 10 is a treatment agent that performs ion exchange with the components in the ion-exchange glass G1 by contacting with the ion-exchange glass G1. The ion-exchange mixture 10 contains a molten salt 101 and an additive 102.

[0039] The molten salt 101 is a salt containing a component that can exchange ions with the components in the ion exchange glass G1, typically an alkali metal nitrate. As the alkali metal nitrate, NaNO3, KNO3, LiNO3, etc. can be cited, and they can be used alone or in a mixture of multiple types. In the present embodiment, an example is given for the case where a mixed salt of NaNO3 and KNO3 is used. The mixing ratio of NaNO3 and KNO3 can be determined arbitrarily, for example, it is set to NaNO3 5-95% and KNO3 5-95% in mass%, preferably NaNO3 30-80% and KNO3 20-70%, and more preferably NaNO3 50-70% and KNO3 30-50%.

[0040] The additive 102 is a substance containing an alkali metal component that can exchange ions with the alkali metal component eluted from the ion-exchange glass G1 into the molten salt 101 during the ion exchange process, and is a metal salt containing a monovalent metal component different from the eluted ions. In the present embodiment, as the alkali metal salt, the additive 102 can use, for example, an alkali metal silicate containing an alkali metal component having an ion radius larger than that of the alkali metal component eluted from the ion-exchange glass G1 into the molten salt 101.

[0041] The type of alkali metal silicate added as additive 102 is preferably appropriately selected according to the alkali metal component dissolved from the ion exchange glass G1 into the molten salt 101. In the first embodiment, the case where the ion exchange glass G1 is lithium aluminum silicate glass and the alkali metal component dissolved into the molten salt 101 is Li ion is used as an example for explanation. In this case, the alkali metal silicate is preferably sodium silicate. The sodium silicate includes at least one selected from Na2SiO3 (sodium metasilicate), Na4SiO4, Na2Si2O5 and Na2Si4O9. The sodium silicate is preferably an anhydrous substance, but it can also be a hydrate. According to such a structure, the Li ions dissolved into the molten salt 101 can be ion-exchanged with the Na ions contained in the alkali metal silicate, thereby suppressing the increase in the concentration of Li ions in the molten salt 101.

[0042] The alkali metal silicate is preferably a crystal. The alkali metal silicate is further preferably a substance in which the alkali metal silicate crystal is made into a powder. The alkali metal salt crystal is preferably in a powdery state at the time of addition to the molten salt, but it can also be crushed in the molten salt after being added to the molten salt to form a powder. In addition, the average particle size D50 of the powder is preferably 10 to 1000 μm. In order to improve the ion exchangeability with the alkali metal component dissolved from the ion exchange glass, the average particle size D50 of the powder is more preferably 900 μm or less, 800 μm or less, 700 μm or less, 500 μm or less, and particularly preferably 450 μm or less. In addition, in order to prevent dust before addition, the average particle size D50 of the powder is more preferably 20 μm or more, 50 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, and particularly preferably 250 μm or more.

[0043] When the molten salt 101 is set to 100 parts by mass, the amount of the additive 102 added to the molten salt 101, that is, the amount of the alkali metal silicate, is preferably measured and added in such a manner that the alkali metal silicate becomes 0.1 to 30 parts by mass. The amount of the alkali metal silicate added is more preferably 1 to 30 parts by mass, 2 to 25 parts by mass, 3 to 20 parts by mass, or 4 to 15 parts by mass. If the amount of the additive 102 added is too small, a sufficient ion adjustment effect cannot be obtained, and if the amount added is too large, the cost of the additive may increase.

[0044] It should be noted that in the first embodiment, as the alkali metal silicate, potassium silicate may be used instead of sodium silicate, or used in combination with sodium silicate. The potassium silicate includes at least one selected from K2SiO3, K4SiO4, K2Si2O5 and K2Si4O9. The potassium silicate is preferably an anhydrous substance, but may also be a hydrate.

[0045] The storage tank 11 is a tank for storing the ion exchange mixture 10. At least a portion of the contact surface of the storage tank 11 with the ion exchange mixture 10 is made of metal. In the first embodiment, the inner surface 11S of the storage tank 11 is made of stainless steel. In addition, the storage layer 11 preferably further includes an opening for taking out and putting in the jig 12 and the ion exchange glass G1 and a cover (not shown) for covering the opening.

[0046] The jig 12 is a member for holding the ion exchange glass G1. During the ion exchange process, the jig 12 is immersed in the ion exchange mixture 10 in the storage tank 11 while holding the ion exchange glass G1. At least a part of the contact surface of the jig 12 that contacts the ion exchange mixture 10 is made of metal. In the first embodiment, the jig 12 is made of stainless steel as a whole. The jig 12 is moved in and out of the storage layer 11 by a conveying device (not shown).

[0047] The ion exchange glass G1 is a glass article before the ion exchange treatment that becomes the object of the ion exchange treatment. In the present first embodiment, the case where the ion exchange glass G1 is in the shape of a rectangular plate is exemplified. The plate thickness of the ion exchange glass G1 is, for example, 2.0 mm or less, more preferably 1.0 mm or less, and further preferably 0.3 mm to 0.9 mm. The length of the ion exchange glass G1 is, for example, 5 mm to 5000 mm, more preferably 15 mm to 1000 mm, 30 mm to 500 mm, 50 mm to 300 mm, and particularly preferably 70 mm to 200 mm, and the width of the ion exchange glass G1 is, for example, 1 mm to 4000 mm, more preferably 10 mm to 1000 mm, 30 mm to 500 mm, 40 mm to 300 mm, and particularly preferably 50 mm to 150 mm.

[0048] As described above, in the first embodiment, the ion exchange glass G1 is an alkali aluminosilicate glass, preferably an alkali aluminosilicate glass containing 1.0 mol% or more of Li2O as a glass composition. For example, as a glass composition, in terms of mass%, it is preferred to contain SiO2 40% to 70%, Al2O3 10% to 30%, B2O3 0% to 3%, Na2O 5% to 25%, K2O0% to 5.5%, Li2O 0.1% to 10%, MgO 0% to 5.5%, and P2O5 2% to 10%.

[0049] Na2O is an ion exchange component, and is also a component that reduces high temperature viscosity and improves solubility and formability. In addition, Na2O is also a component that improves devitrification resistance, formed body refractory, and especially devitrification by reaction with alumina refractory. If the content of Na2O is too little, the solubility decreases, or the thermal expansion coefficient decreases excessively, or the ion exchange rate is prone to decrease. Therefore, the preferred lower limit range of Na2O is 5% or more, 7% or more, 8% or more, 8.5% or more, 9% or more, 9.5% or more, 10% or more, 11% or more, and 12% or more in mass%, and is particularly preferably 12.5% ​​or more. On the other hand, if the content of Na2O is too much, the viscosity of the phase separation is prone to decrease. In addition, the acid resistance decreases, or the lack of component balance of the glass composition will lead to a decrease in devitrification resistance. Therefore, the preferred upper limit range of Na2O is 25% or less, 22% or less, 20% or less, 19.5% or less, 19% or less, 18% or less, 17% or less, 16.5% or less, 16% or less, and 15.5% or less, and particularly preferably 15% or less.

[0050] K2O is a component that reduces high temperature viscosity and improves solubility and formability. Furthermore, it is also a component that improves resistance to devitrification and increases Vickers hardness. However, if the content of K2O is too much, the viscosity is likely to decrease due to phase separation. In addition, there is a tendency for the acid resistance to decrease, or the lack of component balance in the glass composition to reduce the resistance to devitrification. Therefore, the preferred lower limit range of K2O is 0% or more, 0.01% or more, 0.02% or more, 0.1% or more, 0.5% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, and particularly preferably 3.5% or more, and the preferred upper limit range is 5.5% or less, 5% or less, and particularly preferably less than 4.5%.

[0051] Li2O is an ion exchange component, and is also a component that reduces high temperature viscosity and improves solubility and formability. In addition, Li2O is a component that increases Young's modulus. In addition, Li2O is also a component that dissolves during ion exchange treatment and deteriorates the ion exchange solution. Therefore, the preferred lower limit range of Li2O is 0.1% or more, 0.5% or more, 1.0% or more, 1.5% or more, 2.0% or more, and especially 2.5% or more in mass %, and the preferred upper limit range is 10% or less, 8% or less, 5% or less, 4.5% or less, 4.0% or less, and especially less than 3.5%.

[0052] The above-mentioned ion exchange glass G1 can be produced, for example, as follows.

[0053] First, the glass raw materials prepared to have the above-mentioned glass composition are put into a continuous melting furnace, heated and melted at 1500°C to 1600°C, clarified, supplied to a forming device, formed into a plate shape by an overflow down-draw method, and slowly cooled, thereby producing the ion exchange glass G1. In addition to the overflow down-draw method, various forming methods can be used. For example, forming methods such as the float method, the down-draw method (slit down-draw method, re-draw method, etc.), the flattening method, and the pressurization method can be used.

[0054] The ion exchange glass G1 may be bent as required after or while being formed. In addition, it may be cut, drilled, surface polished, chamfered, end polished, etched, and the like as required.

[0055] Hereinafter, a method for producing ion-exchanged glass using the above-mentioned ion-exchanged glass producing apparatus 1 will be described. Figure 2 This is a flowchart showing an outline of the method for producing ion-exchanged glass according to the first embodiment of the present invention.

[0056] First, if Figure 2As shown, the molten salt preparation process is performed (step S1). Specifically, first, NaNO3 and KNO3 are mixed and heated to melt inside the storage layer 11 to prepare the molten salt 101.

[0057] Next, an ion exchange treatment process (step S2) is performed. Specifically, a plurality of ion exchange glasses G1 are held in a fixture 12 as a batch and immersed in a molten salt 101. Conditions such as the temperature of the molten salt and the immersion time in the ion exchange treatment can be determined arbitrarily. The temperature of the molten salt is, for example, 350°C to 500°C, preferably 360°C to 470°C, 360°C to 450°C, 360°C to 430°C, and particularly preferably 360°C to 410°C. In addition, the immersion time is, for example, 0.1 to 30 hours, preferably 0.2 to 20 hours, 0.3 to 15 hours, 0.4 to 10 hours, and particularly preferably 0.5 to 5 hours. By performing an ion exchange treatment on the ion exchange glass G1, an ion exchange glass GX is obtained.

[0058] When the ion exchange treatment of one batch is completed, the ion exchange treatment is performed on the next batch of the ion exchange glass G1, and the ion exchange treatment is repeatedly performed until the ion exchange of a predetermined number of batches is completed (step S3: No).

[0059] On the other hand, when the predetermined number of batches of ion exchange are completed (step S3: Yes), the stress characteristics of the ion exchange glass GX obtained in the final ion exchange treatment are measured (step S4). Specifically, the surface compressive stress CS of the ion exchange glass GX is measured using a stress measuring device.

[0060] It should be noted that in the present invention, stress characteristics can be measured using a known stress measurement method and a known stress measurement device. For example, surface stress meters FSM-6000LE and SLP-1000 manufactured by Orihara Manufacturing Co., Ltd. can be used alone or in combination.

[0061] After the stress characteristic measurement is completed, it is determined whether the stress characteristic is less than a predetermined threshold value (step S5). It should be noted that the value of the threshold value can be arbitrarily set according to product specifications and measuring devices, for example, it can be set to any value within the range of 300 to 1000 MPa. Specifically, in the first embodiment, for example, it is determined whether the value of the surface compressive stress CS is less than 400 MPa. More preferably, when the value of the surface compressive stress CS of the initial batch of ion-exchanged glass GX is set to 100%, it is preferred to set the compressive stress value of 75 to 85% as the threshold value.

[0062] When the stress characteristic is equal to or greater than the predetermined threshold value (step S5 : No), the next batch of ion exchange treatment is performed, and the above-mentioned processes from step S2 to step S5 are repeated.

[0063] On the other hand, when the stress characteristic is less than the predetermined threshold value ("Yes" in step S5), an addition process of adding an alkali metal silicate as an additive 102 to the molten salt 101 is performed (step S6). By this addition process, the ion exchange mixture 10 of the present invention is formed inside the storage tank 11.

[0064] In addition, in step S6, it is preferred that after the additive 102 is added to the molten salt 101, the molten salt 101 is stirred. The stirring can be performed by inserting a rod, a paddle, etc. into the receiving tank 11 and performing manual or mechanical automatic operation. In addition, after stirring, the next treatment can be performed in a state where the additive has been dispersed in the molten salt 101, or the additive 101 can be left to standby until it is precipitated at the inner bottom of the receiving tank 11.

[0065] After the addition process of step S6 is completed, the process of step S2 is performed on the next batch of ion exchange glass G1, and the above process is repeated. In addition, after the process of step S6, a predetermined waiting time for the additive 102 to adjust the ion concentration to a certain extent can be set, and the process of step S2 is started after the waiting time has passed. After the process of step S6, the waiting time until the start of step S2 can be set arbitrarily, for example, more than 1 minute, preferably more than 5 minutes, more than 10 minutes, more than 30 minutes, 1 hour to 24 hours, and particularly preferably 1 hour to 12 hours.

[0066] According to the method for producing ion-exchanged glass of the first embodiment described above, the ion-exchange mixture 10 is formed by adding alkali metal silicate as the additive 102 to the molten salt 101, so that the ion balance of the molten salt 101 can be adjusted to an appropriate state. In addition, by adding alkali metal silicate as the additive 102, corrosion of the receiving tank 11 and the jig 12 can be suppressed. Therefore, the stress characteristics of the obtained ion-exchanged glass GX can be stabilized.

[0067] Furthermore, according to the method for producing the ion-exchanged glass of the first embodiment, by adding the additive 102 at an appropriate timing, it is possible to prevent excessive addition of the additive 102 and to more appropriately adjust the ion balance of the molten salt 101 .

[0068] In addition, in the ion exchange glass manufacturing method of the first embodiment described above, the case where the surface compressive stress CS is measured as a stress characteristic and whether the addition treatment needs to be implemented is determined based on the size of the surface compressive stress CS value, but the above-mentioned treatment can also be performed based on other stress characteristics. For example, the depth DOC of the compressive stress layer can also be measured in step S4, and it can be determined in step S5 whether the depth of the compressive stress layer is less than a predetermined threshold. In this case, the threshold value of the depth DOC of the compressive stress layer can be set to any value in the range of 50 to 150 μm, for example. In addition, the threshold value of the depth DOC of the compressive stress layer can also be set based on a ratio corresponding to the thickness of the glass G1 for ion exchange. In this case, the threshold value of the depth DOC of the compressive stress layer can be set to any value in the range of 10% to 25% of the thickness of the glass G1 for ion exchange, for example.

[0069] In addition, in the ion exchange glass manufacturing method of the first embodiment, the case where the so-called sampling inspection is performed according to the specified number of batches is exemplified, but the measurement process can also be performed each time the ion exchange treatment is performed on each batch of ion exchange glass G1. In this case, the determination process of step S3 can be omitted. If such a process is adopted, the addition process of step S6 can be performed at an appropriate time, and the outflow of defective products can be more appropriately suppressed.

[0070] In addition, in the ion exchange glass manufacturing method of the first embodiment, the processing of steps S4 and S5 can also be omitted. That is, the addition processing of step S6 can also be implemented at the moment when the ion exchange processing of the specified number of batches is completed ("Yes" in step S3). For example, in the case where the degree of degradation of the molten salt 101 and the degree of decline in the characteristics of the ion exchange glass GX can be predicted by the number of batches, by adopting such a processing, the man-hours of steps S4 and S5 can be reduced and the production efficiency can be improved.

[0071] In the ion-exchanged glass manufacturing method of the first embodiment, after the molten salt preparation step of step S1 and before the ion exchange treatment of step S2, the addition treatment of step S6 may be performed to start production in a state where the additive 102 is added to the molten salt 101 in advance.

[0072] (Second Embodiment)

[0073] In the first embodiment described above, the case of suppressing the increase in the concentration of Li ions dissolved in the molten salt is described as an example, but it can also be applied to the adjustment of other ion concentrations. For example, in the case of suppressing the increase in the concentration of Na ions dissolved in the molten salt, it can be applied as in the following second embodiment. It should be noted that the following is a description of the differences from the first embodiment, and the other structures are the same as the first embodiment, and the description is omitted.

[0074] The ion exchange glass G2 of the second embodiment of the present invention is an alkali aluminosilicate glass containing Na2O as a glass composition and not containing Li2O. The ion exchange glass G2 is preferably an alkali aluminosilicate glass containing 1.0 mol% or more of Na2O as a glass composition. More specifically, the ion exchange glass G2 is, for example, a glass containing SiO2 40% to 70%, Al2O3 10% to 30%, B2O3 0% to 3%, Na2O 5% to 25%, K2O 0% to 5.5%, MgO 0% to 5.5%, P2O5 2% to 10% as a glass composition, and not containing Li2O. It should be noted that in the present invention, not containing Li2O means that the content of Li2O is less than 0.1% by mass.

[0075] Na2O is an ion exchange component, and is also a component that reduces high temperature viscosity and improves solubility and formability. In addition, Na2O is also a component that improves devitrification resistance, formed body refractory, and especially devitrification of reaction with alumina refractory. If the content of Na2O is too little, the solubility decreases, or the thermal expansion coefficient decreases excessively, or the ion exchange rate is easy to decrease. Therefore, the preferred lower limit range of Na2O is 5% or more, 7% or more, 8% or more, 8.5% or more, 9% or more, 9.5% or more, 10% or more, 11% or more, and 12% or more in mass%, and is particularly preferably 12.5% ​​or more. On the other hand, if the content of Na2O is too much, the viscosity of the phase separation is easy to decrease. In addition, there is a tendency that the acid resistance decreases, or the component balance of the glass composition is lacking, and the devitrification resistance decreases instead. Therefore, the preferred upper limit range of Na2O is 25% or less, 22% or less, 20% or less, 19.5% or less, 19% or less, 18% or less, 17% or less, 16.5% or less, 16% or less, and 15.5% or less, and particularly preferably 15% or less.

[0076] K2O is a component that reduces high temperature viscosity and improves solubility and formability. Furthermore, it is also a component that improves resistance to devitrification and increases Vickers hardness. However, if the content of K2O is too much, the viscosity is likely to decrease due to phase separation. In addition, there is a tendency for acid resistance to decrease, or there is a lack of component balance in the glass composition, which in turn causes resistance to devitrification to decrease. Therefore, the preferred lower limit range of K2O is, in mass %, 0% or more, 0.01% or more, 0.02% or more, 0.1% or more, 0.5% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, and particularly preferably 3.5% or more, and the preferred upper limit range is 5.5% or less, 5% or less, and particularly preferably less than 4.5%.

[0077] In the second embodiment, the alkali metal silicate as an additive contained in the mixture for ion exchange is preferably a potassium silicate. The potassium silicate includes at least one selected from K2SiO3, K4SiO4, K2Si2O5 and K2Si4O9. According to such a configuration, the Na ions dissolved into the molten salt can be ion-exchanged with the K ions contained in the alkali metal silicate, thereby suppressing the increase in the Na ion concentration in the molten salt.

[0078] Potassium silicate is particularly effective when added to a molten salt with KNO3 as the main component. The molten salt 101 with KNO3 as the main component contains, for example, KNO3 80-100% and NaNO3+LiNO3 0-20% by mass%, preferably KNO3 90-99.9% and NaNO3+LiNO3 0.1-10%, and more preferably KNO3 98.5-99.8% and NaNO3+LiNO3 0.2-1.5%. In such a molten salt with KNO3 as the main component, Na ions are dissolved from the glass, and the Na ion concentration in the molten salt is easily increased. Therefore, by adding the above-mentioned potassium silicate, the concentration increase can be effectively suppressed.

[0079] (Third Embodiment)

[0080] In the second embodiment, the case of using potassium silicate as an additive contained in the ion exchange mixture is described, but in order to suppress the increase in the Na ion concentration of the molten salt, a lithium salt may be used as an additive. That is, a metal salt containing a metal component having an ion radius smaller than that of the eluted ion may be used as an additive.

[0081] The ion exchange glass according to the third embodiment preferably contains Na 2 O as a glass composition and contains a lithium salt as an additive contained in the ion exchange mixture.

[0082] The lithium salt is, for example, a lithium silicate salt, comprising at least one selected from Li2SiO3 (lithium metasilicate), Li4SiO4, Li2Si2O5, and Li2Si4O9. According to such a configuration, the Na ions dissolved into the molten salt can be ion-exchanged with the Li ions contained in the alkali metal silicate, thereby suppressing the increase in the Na ion concentration in the molten salt.

[0083] In addition, lithium phosphate salts may also be used as lithium salts. The lithium phosphate salts include at least one selected from Li3PO4 (trilithium phosphate), Li2HPO4 and LiH2PO4. Lithium silicate salts and lithium phosphate salts may be used alone or in combination.

[0084] In addition, in the third embodiment, the same ion exchange glass and molten salt as those described in the first and second embodiments can be used under the same conditions.

[0085] (Fourth Embodiment)

[0086] The ion exchange glass GX obtained in the first embodiment may be further subjected to an additional ion exchange treatment. Figure 2 The ion exchange treatment (step S2) shown is used as the ion exchange treatment of the first stage, and the ion exchange treatment of the second stage not shown is further implemented. In the ion exchange treatment of the second stage, it is preferred to prepare a molten salt (called the second molten salt) with a high mixing ratio of KNO3 compared to the molten salt 101 (called the first molten salt) used in the ion exchange treatment of the first stage for use, and the second molten salt is more preferably KNO3. The mixing ratio is more than 90% by mass, and the second molten salt is further preferably a molten salt composition described in the second embodiment. According to such treatment, for the ion exchange glass GX, a deep compressive stress layer can be formed in the ion exchange treatment of the first stage, and a high surface compressive stress CS is given in the ion exchange treatment of the second stage. It should be noted that the ion exchange treatment of the second stage preferably adjusts the composition, treatment temperature and treatment time of the molten salt so that the surface compressive stress CS of the ion exchange glass GX reaches more than 700MPa.

[0087] In addition, potassium silicate or lithium salt may be added to the second molten salt used in the second stage ion exchange treatment in the same manner as in the second and third embodiments. According to such a structure, excessive increase in Na ion concentration can be suppressed in the second molten salt.

[0088] In addition, for the second molten salt, sodium silicate salt can also be added in the same manner as the method shown in the first embodiment. In the case where the lithium salt is attached to the glass surface by the first stage ion exchange treatment and the glass is directly immersed in the second molten salt for the second stage ion exchange treatment, in the second molten salt, the Li ion concentration may increase, hindering the ion exchange. However, as described above, by adding sodium silicate salt to the second molten salt, the increase in the Li ion concentration in the second molten salt can be suppressed.

[0089] In the above embodiments, the ion exchange glass G1 and the ion exchange glass GX are rectangular plates, but are not limited to rectangular plates and may be applied to any shapes such as curved plates, disks, tubes, containers, or spheres.

[0090] In addition, in the above-mentioned embodiments, examples are given of cases where the ion exchange treatment is mainly for the purpose of improving the strength of the glass and the ion exchange glass GX is chemically strengthened glass. However, the present invention can also be applied to ion exchange treatments corresponding to other purposes, such as ion exchange treatments for the purpose of adjusting the refractive index of optical components such as lenses, surface treatment of glass for medical purposes, etc.

[0091] In addition, the alkali metal silicate used as the additive 102 may be a mixture of potassium silicate, sodium silicate, and lithium silicate. For example, when a plurality of alkali metal ions are eluted from the ion exchange glass G1, the concentration of each alkali metal ion in the molten salt 101 can be appropriately adjusted by mixing a plurality of alkali metal silicates according to the number of types of alkali metal ions eluted.

[0092] In addition, in the above-mentioned embodiments, the case where stainless steel is used in the receiving tank 11 and the clamp 12 is exemplified, but as the stainless steel, austenitic stainless steel, ferritic stainless steel and other known types of stainless steel can be used. In addition, the receiving tank 11 and the clamp 12 can also be composed of any metal that is corrosion-resistant to the molten salt 101 in addition to stainless steel.

[0093] [Example 1]

[0094] Hereinafter, the method for producing the ion-exchange glass and the mixture for ion exchange of the present invention will be described based on examples. It should be noted that the following examples are merely illustrative, and the present invention is not limited to the following examples at all.

[0095] The sample was prepared as follows: First, as a glass composition, an ion exchange glass G1 containing, by mass%, 51.6% SiO2, 27.9% Al2O3, 0.3% B2O3, 0.6% K2O, 7.5% Na2O, 3.3% Li2O, 0.3% MgO, 8.4% P2O5, and 0.1% SnO2 was prepared.

[0096] Specifically, glass raw materials were blended to the above composition and melted in a platinum pot at 1600° C. for 21 hours. The obtained molten glass was then formed into a plate having a thickness of 0.7 mm by flowing down from a refractory forming body using an overflow down-draw method.

[0097] Next, the ion exchange treatment was performed by immersing the ion exchange glass in the ion exchange mixtures having the compositions shown in No. 1 to 6 shown in Table 1 under the conditions of temperature and time shown in Table 1. In Table 1, No. 1 to 3 are examples of the present invention, and No. 4 to 6 are comparative examples.

[0098] In the ion exchange mixtures of No. 1, No. 2, and No. 4, LiNO3 was mixed in the molten salt to simulate the molten salt with increased Li ion concentration after repeated ion exchange treatment. On the other hand, the ion exchange mixtures of No. 3, No. 5, and No. 6 are molten salts in a new state without containing Li ions.

[0099] In the ion exchange mixtures of No. 1 to 3, Na2SiO3 was added as an additive. On the other hand, in the ion exchange mixtures of No. 4 and No. 6, no additive was added for comparison. In addition, in the ion exchange mixture of No. 5, Na3PO4 was added as an additive for comparison. It should be noted that in Table 1, the amount of additive added is expressed by mass parts when the molten salt is set to 100 mass parts.

[0100] In order to evaluate metal corrosion resistance, a plate-shaped metal specimen made of SUS304, SUS316 and SUS430 and having a thickness of 1.0 mm, a width of 20 mm and a length of 50 mm was immersed in each of the ion exchange mixtures No. 3 and No. 5, respectively.

[0101] Table 1 shows the properties of the ion-exchange mixture and ion-exchange glass obtained in this manner.

[0102] [Table 1]

[0103]

[0104] The surface compressive stress CS in Table 1 is a value measured using a surface stress meter FSM-6000LE manufactured by Orihara Manufacturing Co., Ltd.

[0105] The metal corrosion amount in Table 1 indicates the amount of change in weight of each metal sample after immersion in the ion exchange mixture relative to the weight before immersion.

[0106] Compared with Comparative Example No. 6 in which the molten salt contained no Li ions, Comparative Example No. 4 in which the molten salt had a high Li ion concentration and contained no additives showed a significant decrease in the surface compressive stress value CS of the ion-exchanged glass.

[0107] On the other hand, it can be confirmed that both Examples Nos. 1 and 2 containing Na 2 SiO 3 as an additive suppress the decrease in the surface compressive stress value CS of the ion-exchanged glass, as compared with Comparative Example No. 4 containing no additive.

[0108] In addition, in Comparative Example No. 5, in which Na3PO4 was added as an additive, the weight of each metal sample after immersion was confirmed to be reduced, and the occurrence of metal corrosion was confirmed. On the other hand, in Example No. 3, in which Na2SiO3 was added as an additive, it was confirmed that the weight of the metal sample was not reduced, and metal corrosion was suppressed.

[0109] [Example 2]

[0110] In the following examples, the effect of suppressing the increase in the Na ion concentration in the molten salt by adding a lithium salt was verified. In Table 2, No. 7 is an example of the present invention, No. 8 is a reference example, and No. 9 is a comparative example.

[0111] First, molten salts having the compositions shown in Nos. 7 to 9 shown in Table 2 were adjusted to the temperatures shown in Table 1. The molten salts according to Nos. 7 to 9 were prepared by mixing NaNO 3 in the molten salts in order to simulate molten salts in which the Na ion concentration increases after repeated ion exchange treatment.

[0112] Next, each additive listed in Table 2 was added to each molten salt to prepare an ion exchange mixture. In the ion exchange mixture No. 7, Li2SiO3 was added as an additive. In the ion exchange mixture No. 8, Li3PO4 was added as an additive. On the other hand, in the ion exchange mixture No. 9, no additive was added for comparison. It should be noted that in Table 2, the amount of additive added is expressed by mass parts when the molten salt is set to 100 mass parts.

[0113] Next, the Li ion concentration and Na ion concentration of the ion exchange mixture were measured after the time described in Table 2 had passed since the addition of the additive. More specifically, about 10 g of the supernatant without precipitate was collected from each molten salt, and the concentrations of Li ions and Na ions were quantitatively analyzed using atomic absorption spectrometry.

[0114] [Table 2]

[0115]

[0116] According to the measurement results, the Na ion concentration in the ion exchange mixture according to Example No. 7 was lower than that in Comparative Example No. 9 containing no additive, and the effect of suppressing the increase in the Na ion concentration was confirmed.

[0117] Industrial Applicability

[0118] The method for producing ion-exchanged glass, the apparatus for producing ion-exchanged glass, and the mixture for ion exchange of the present invention can be used, for example, for producing ion-exchanged glass used in smartphones, mobile phones, tablet computers, personal computers, digital cameras, touch panel displays, cover glasses of other display devices, vehicle panels, magnetic disks, and the like.

Claims

1. A method for producing ion exchange glass, characterized in that: The method for producing ion-exchange glass comprises the step of immersing a part or all of ion-exchange glass containing an alkali metal component in an ion-exchange mixture to perform an ion-exchange treatment. The ion exchange mixture contains a molten salt and an alkali metal silicate. The alkali metal silicate contains an alkali metal component that can undergo ion exchange with an alkali metal component eluted from the ion exchange glass into the molten salt during the ion exchange treatment. wherein the alkali metal component eluted from the ion exchange glass into the molten salt during the ion exchange treatment is Na ion, The alkali metal silicate comprises at least one selected from Li2SiO3, Li4SiO4, Li2Si2O5 and Li2Si4O9, and The molten salt contains KNO3 80-100% by mass and NaNO3+LiNO3 0-20% by mass.

2. The method for producing ion-exchanged glass according to claim 1, wherein: The ion exchange glass is alkali aluminosilicate glass and contains 1.0 mol % or more of Na2O as a composition of the ion exchange glass. The molten salt contains KNO3.

3. The method for producing ion-exchanged glass according to claim 1, wherein: The alkali metal silicate is a powdery alkali metal silicate crystal.

4. The method for producing ion-exchanged glass according to claim 3, wherein: The average particle size D50 of the powdery alkali metal silicate is 10 to 1000 μm.

5. The method for producing ion-exchanged glass according to claim 3, wherein: The method for producing the ion-exchanged glass further includes a step of stirring the molten salt after adding the alkali metal silicate to the molten salt.

6. The method for producing ion-exchanged glass according to claim 4, wherein: The method for producing the ion-exchanged glass further includes a step of stirring the molten salt after adding the alkali metal silicate to the molten salt.

7. The method for producing ion-exchanged glass according to any one of claims 1 to 6, wherein: When the molten salt is 100 parts by mass, the amount of the alkali metal silicate added is 0.1 to 30 parts by mass.

8. The method for producing ion-exchanged glass according to any one of claims 1 to 6, wherein: The ion exchange treatment is performed multiple times by sequentially immersing different batches of the ion exchange glass in the ion exchange mixture. The method for manufacturing the ion exchange glass further comprises: After a predetermined number of batches of the ion-exchange glass have been subjected to the ion-exchange treatment, the step of measuring stress characteristics of the ion-exchanged glass obtained in the final ion-exchange treatment; and A step of determining whether to add the alkali metal silicate to the molten salt based on the measurement result of the stress characteristic.

9. The method for producing ion-exchanged glass according to claim 8, wherein: The surface compressive stress of the glass is measured as the stress characteristic. When the surface compressive stress is less than a predetermined threshold value, after adding the alkali metal silicate to the molten salt, ion exchange of the next batch of the ion exchange glass is performed, When the surface compressive stress is equal to or greater than a predetermined threshold value, ion exchange of the next batch of the glass for ion exchange is performed without adding the alkali metal silicate to the molten salt.

10. A mixture for ion exchange, wherein: The ion exchange mixture contains a molten salt and an additive. The molten salt contains KNO3, As the additive, an alkali metal silicate is contained, wherein the alkali metal component eluted from the ion exchange glass into the molten salt during the ion exchange treatment is Na ion, The alkali metal silicate comprises at least one selected from Li2SiO3, Li4SiO4, Li2Si2O5 and Li2Si4O9, and The molten salt contains KNO3 80-100% by mass and NaNO3+LiNO3 0-20% by mass.

11. The ion exchange mixture according to claim 10, wherein When the molten salt is 100 parts by mass, 0.1 to 30 parts by mass of the alkali metal silicate is contained as the additive.

12. The ion exchange mixture according to claim 10 or 11, wherein The alkali metal silicate is a powdery alkali metal silicate crystal.

13. An ion exchange glass manufacturing device, characterized in that: have: The ion exchange mixture according to any one of claims 10 to 12; and a storage tank for storing the ion exchange mixture, At least a portion of a surface of the storage tank that contacts the ion exchange mixture is made of metal.

14. The ion exchange glass manufacturing apparatus according to claim 13, wherein: The ion-exchange glass manufacturing apparatus further includes a jig that holds the ion-exchange glass and is immersed in the ion-exchange mixture. The contact surface of the jig with the ion exchange mixture is made of metal.

15. The ion exchange glass manufacturing apparatus according to claim 13 or 14, wherein: The metal is stainless steel.

Citation Information

Patent Citations

  • Methods for regenerating lithium-enriched salt baths

    US20180362399A1

  • Strengthened glass articles

    GB1094431A